Evaluation of health workforce competence in maternal and neonatal issues in public health sector of Pakistan: an Assessment of their training needs - Ariff, Shabina; Soofi, Sajid B; Sadiq, Kamran; Feroze, Asher B; Khan, Shuaib; Jafarey, Sadiqua N; Ali, Nabeela; Bhutta, Zulfiqar A (BMC health services research, 2010)
Background More than 450 newborns die every hour worldwide, before they reach the age of four weeks (neonatal period) and over 500,000 women die from complications related to childbirth. The major direct causes of neonatal death are infections (36%), Prematurity (28%) and Asphyxia (23%). Pakistan has one of the highest perinatal and neonatal mortality rates in the region and contributes significantly to global neonatal mortality. The high mortality rates are partially attributable to scarcity of trained skilled birth attendants and paucity of resources. Empowerment of health care providers with adequate knowledge and skills can serve as instrument of change. Methods We carried out training needs assessment analysis in the public health sector of Pakistan to recognize gaps in the processes and quality of MNCH care provided. An assessment of Knowledge, Attitude, and Practices of Health Care Providers on key aspects was evaluated through a standardized pragmatic approach. Meticulously designed tools were tested on three tiers of health care personnel providing MNCH in the community and across the public health care system. The Lady Health Workers (LHWs) form the first tier of trained cadre that provides MNCH at primary care level (BHU) and in the community. The Lady Health Visitor (LHVs), Nurses, midwives) cadre follow next and provide facility based MNCH care at secondary and tertiary level (RHCs, Taluka/Tehsil, and DHQ Hospitals). The physician/doctor is the specialized cadre that forms the third tier of health care providers positioned in secondary and tertiary care hospitals (Taluka/Tehsil and DHQ Hospitals). The evaluation tools were designed to provide quantitative estimates across various domains of knowledge and skills. A priori thresholds were established for performance rating. Results The performance of LHWs in knowledge of MNCH was good with 30% scoring more than 70%. The Medical officers (MOs), in comparison, performed poorly in their knowledge of MNCH with only 6% scoring more than 70%. All three cadres of health care providers performed poorly in the resuscitation skill and only 50% were able to demonstrate steps of immediate newborn care. The MOs performed far better in counselling skills compare to the LHWs. Only 50 per cent of LHWs could secure competency scale in this critical component of skills assessment. Conclusions All three cadres of health care providers performed well below competency levels for MNCH knowledge and skills. Standardized training and counselling modules, tailored to the needs and resources at district level need to be developed and implemented. This evaluation highlighted the need for periodic assessment of health worker training and skills to address gaps and develop targeted continuing education modules. To achieve MDG4 and 5 goals, it is imperative that such deficiencies are identified and addressed.